2005
DOI: 10.1038/sj.leu.2403977
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to cytarabine and gemcitabine and in vitro selection of transduced cells after retroviral expression of cytidine deaminase in human hematopoietic progenitor cells

Abstract: Overexpression of the detoxifying enzyme cytidine deaminase (CDD) renders normal and leukemic hematopoietic cells resistant to cytarabine (1-b-D-arabinofuranosylcytosine), and studies on murine cells have suggested transgenic CDD overexpression as a way to reduce the substantial myelotoxicity induced by the deoxycytidine analogs cytarabine and gemcitabine (2 0 ,2 0 -difluorodeoxycytidine). We now have investigated CDD (over-)expression in the human hematopoietic system. Retroviral gene transfer significantly i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 28 publications
3
35
0
Order By: Relevance
“…Previous research also demonstrated a decreased activity of dCyd analogues such as gemcitabine and cytarabine (araC; an antitumor drug that is also subject to deamination) in Cyd deaminaseoverexpressing human tumor cells (40,41) and progenitor cells (42). The activity of such antitumor molecules could be counteracted by co-administration of THU (40).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research also demonstrated a decreased activity of dCyd analogues such as gemcitabine and cytarabine (araC; an antitumor drug that is also subject to deamination) in Cyd deaminaseoverexpressing human tumor cells (40,41) and progenitor cells (42). The activity of such antitumor molecules could be counteracted by co-administration of THU (40).…”
Section: Discussionmentioning
confidence: 99%
“…14 To generate high-titer ecotropic producer cell lines, supernatant from these PG13 producer clones was used for transduction of FNX-eco cells. 17 FNX-eco cells (3 ϫ 10 4 ) were cultured in 6-well plates in DMEM supplemented with 10% FCS, 2 mM L-glutamine, 100 U/mL penicillin and 100 U/mL streptomycin (P/S), and 20 mM HEPES (all from Sigma-Aldrich, Taufkirchen, Germany), and were incubated with 1 mL supernatant for 4 hours in the presence of 8 g/mL Polybrene (1,5-dimethyl-1,5-diazaundecamethylene polymethobromide, hexadimethrine bromide; Sigma-Aldrich) for 3 times on 3 consecutive days.…”
Section: Retroviral Vectors Producer Cell Lines and Virus Productionmentioning
confidence: 99%
“…13 More recently, our group has investigated CDD gene transfer into primary human hematopoietic cells demonstrating significant resistance to cytarabine and gemcitabine as well as successful in vitro selection of transduced progenitor cells following retrovirally mediated gene transfer and cytarabine application. 14 Studies investigating CDD gene transfer in relevant murine in vivo models, however, are scarce and so far have failed to define the exact myeloprotective potential of this approach. Although one study demonstrated long-term expression of the CDD transgene in the hematopoietic system but did not address in vivo hematoprotection, 15 successful treatment of a lymphoma cell line with a combination of methotrexate and cytarabine in NOD/SCID mice given transplants with drug-resistant murine bone marrow was demonstrated in another model.…”
Section: Introductionmentioning
confidence: 99%
“…CDD represents a clinically highly relevant CTX-R gene, as overexpression of this enzyme protects lymphohematopoietic cells from deoxycytidine analogs such as cytosine-arabinoside (1-b-D-arabinofuranosylcytosine, Ara-C), the most effective single-agent in the treatment of acute leukemias. Myeloprotection as well as chemoselection by hCDD gene transfer has been established in murine and human clonogenic progenitor cells [21][22][23] as well as in murine in vivo bone marrow transplant models [24][25][26]. However, in leukemias, HSC-based myeloprotective gene therapy approaches always carry the risk of inadvertent transduction of malignant cells.…”
Section: Introductionmentioning
confidence: 99%